Analysis of Physical Literacy Measurement in Physical Education for Early Childhood - Feida Noorliala Istiadah; Rahmat Permana (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The problem and research question in this study is how to measure Physical Literacy (PL) skills, especially in early childhood, especially since teachers' perceptions of PL are still limited to theories and concepts. This article aims to analyze PL measurement tools for early childhood, as library material for AUD teaching staff. The research approach used was a literature review. This approach was chosen because the data collected was secondary data. Data collection is done by determining keywords which are then searched through reputable scientific databases. The data that has been obtained is analyzed using a two-themed approach, namely PL Assessment in Concept and Practice by sorting out Scopus Q1 reputable international journals and well-known publishers. The results of the analysis show that practically there are 5 journals and 2 journals conceptually for early childhood in the age range category 8-12 years so that it can be called big children or later chillhood. While in early chilhood the research that develops is still on the discussion of concepts, characteristics and how teaching teachers understand to better understand the concept of PL as a whole.